Facile synthesis of fluorescent polyaniline microspheres and their use for the detection of mercury ions1. (27th August 2015) - Wang, Xiufang; Xuan, Han; Zhang, Jun; Chen, Shaohua; Zhang, Fengjun; Zou, Wensheng
<x xml:space="preserve">Abstract</x> Bright blue fluorescent polyaniline microspheres were prepared by a simple controlled oxidation under mild conditions. A simple, highly sensitive fluorometric Hg2+ probe has been constructed.